Qohelet's concept of deity: A comparative-philosophical perspective - Gericke, Jaco (Verbum et ecclesia, 2013)
This article discusses the concept of deity in the book of Ecclesiastes (Qohelet) from the perspective of issues of interest in analytic philosophy of religion. Of concern are assumptions in the text about religion, the nature of religious language, religious epistemology, the concept of revelation, the attributes of the divine, the existence of God, the problem of evil, the relation between religion and morality and religious pluralism. A comparative philosophical clarification is offered with the aim of discerning similarities and differences between popular views in Christian philosophical theology and what, if anything, Qohelet took for granted on the same issues.